2022
DOI: 10.3389/fpls.2022.916282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fusarium Head Blight Resistance in 410 Chinese Wheat Cultivars Selected for Their Climate Conditions and Ecological Niche Using Natural Infection Across Three Distinct Experimental Sites

Abstract: Exploiting wheat cultivars with stable resistance to Fusarium Head blight (FHB) and toxin accumulation is a cost-effective and environmentally friendly strategy to reduce the risk of yield losses and contamination with mycotoxins. To facilitate the deployment of stable cultivar resistance, we evaluated FHB resistance and resistance to mycotoxin accumulation in 410 wheat lines bred by local breeders from four major wheat growing regions in China after natural infection at three distinct locations (Hefei, Yangzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Our analyses confirmed previous results that FHB severity and toxin production are correlated in wheat and barley ( Choo et al, 2004 ; Geddes et al, 2008 ; He et al, 2015 ; Yan et al, 2022 ). Unlike the previous studies, we used both F. asiaticum and F. graminearum at the same time and were able to compare these species.…”
Section: Discussionsupporting
confidence: 91%
“…Our analyses confirmed previous results that FHB severity and toxin production are correlated in wheat and barley ( Choo et al, 2004 ; Geddes et al, 2008 ; He et al, 2015 ; Yan et al, 2022 ). Unlike the previous studies, we used both F. asiaticum and F. graminearum at the same time and were able to compare these species.…”
Section: Discussionsupporting
confidence: 91%
“…Disease resistance evaluation in multiple environments prevents errors caused by a single environmental factor. Therefore, resistance evaluations are necessary across multiple years or locations (Buerstmayr et al, 2008; Yan et al, 2022). Cluster analysis is a method for dividing a group of objects into classes so that similar objects are in the same class (Gupta et al, 2022; Kalogiouri et al, 2021), while discriminant analysis is a multivariate analysis used to find the linear combination of features that distinguish two or more classes (Huberty, 1975; Stella, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 249 lines/varieties evaluated for FHB reactions, only 2.4% of them displayed a high level of resistance and 13.6% a moderate level of resistance as compared with 60% of them that showed moderate to high levels of FHB susceptibility ( Supplementary Table S1 ). We used the VRI of the check varieties/lines with modified threshold values described in previous studies ( Yan et al., 2020 ; Yan et al., 2022 ) to assign each tested variety/line to the different resistance categories. In contrast to Yan et al (2020 , 2022) who classified entries with a VRI of< 10% into highly resistant and 10-25% as moderately resistant, we considered lines and varieties with a VRI of <7% as highly resistant and those with 10-20% as moderately resistant.…”
Section: Discussionmentioning
confidence: 99%
“…We used the VRI of the check varieties/lines with modified threshold values described in previous studies ( Yan et al., 2020 ; Yan et al., 2022 ) to assign each tested variety/line to the different resistance categories. In contrast to Yan et al (2020 , 2022) who classified entries with a VRI of< 10% into highly resistant and 10-25% as moderately resistant, we considered lines and varieties with a VRI of <7% as highly resistant and those with 10-20% as moderately resistant. The proportion of lines and varieties that were considered highly and moderately resistant agree with a previous study that reported 2.3%, 15.5%, 41.1%, and 41.1% of the wheat samples that expressed high resistance, moderate resistance, moderate susceptibility, and high susceptibility, respectively ( Yan et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation